The Issue of Updating the Real Estate Cadastre in the Field of Land Use in Connection with the Construction of a Building - Karabin‑Zych, Magdalena (Geomatics and Environmental Engineering, 2021)
From the year 2014 to July 31, 2020, setting out a building was surveying work subject to the obligation to report to the locally competent district governor (starosta) before it was commenced. After completion of the building setting out, the contractor of surveying works was obliged to notify the authorities of the completion of the surveying works and to submit the results of surveying works connected with the building setting out. Since July 31, 2020, following the amended Geodesic and Cartographic Law, the obligation to report the building setting out has been repealed. Despite that, the real estate owner will still be obliged to submit an appropriate application to the starost to disclose the new land use in accordance with Article 22 of the Geodesic and Cartographic Law. The author has analysed 31 documentation sets, being the results of building setting out procedures. The analysis verified the size of a land parcel on which the buildings were set out, what land use was presented before setting out and what land use was presented after the building setting out. In addition, the current state of development of the land parcel (as of July 2020) was examined using map portals, and an orthophotomap was used to check whether the building was constructed, in order to verify whether the real estate cadastre was updated further.